Evidence for Enhanced Cellular Uptake and Binding of Thyroxine In Vivo during Acute Infection with Diplococcus pneumoniae - DeRubertis, Frederick R. (1972)
Previous work has demonstrated that acute pneumococcal infections in man and in the rhesus monkey are accompanied by accelerated metabolic disposal of L-thyroxine (T(4)). In order to study the influence of acute pneumococcal infection on the kinetics of hormone distribution, the early cellular uptake of T(4) (CT(4)), reflecting the net effect of plasma and cellular binding factors, was assessed in rhesus monkeys from the differences in instantaneous distribution volumes of T(4)-(131)I and albumin-(125)I during the first 60 min after their simultaneous injection. Hepatic and renal uptakes of (131)I were also determined. Plasma binding of T(4) was assessed by measuring the per cent of free T(4) (% FT(4)) in serum. Six monkeys were studied 12 hr (INF-12) and seven 24 hr (INF-24) after intravenous inoculation with Diplococcus pneumoniae; seven controls were inoculated with a heat-killed culture. CT(4) at 60 min as per cent administered dose was 31.5 ±2.0 (mean ±SE) in INF-12 and 33.0±0.8 in INF-24, values significantly greater than control (22.4±1.3). By contrast, mean% FT(4) was identical in control and INF-12 (0.028 ±0.002 and 0.028 ±0.001) and variably increased in INF-24 (0.034 ±0.003). Thus, in the infected monkeys CT(4) and% FT(4) were not significantly correlated. The increased CT(4) in the infected monkeys could not be ascribed to an increase in vascular permeability and did not correlate with the magnitude of fever. Although the increased CT(4) could not be accounted for by increased hepatic or renal uptake of hormone, hepatic and renal T(4) spaces were increased, results consistent with increased binding by these tissues. Our data indicate that the cellular uptake of T(4) is increased early in acute pneumococcal infection and suggest that this results from a primary enhancement of cell-associated binding factors for T(4).